Legal awareness and the role of market traders in waste management in Simpang Limun market environment in Medan city - Ariman Sitompul; Ruslan; Nurhayati (Trigin Publisher, 2023)
Legal awareness and the role of traders in Waste Management in the traditional market of Simpang jeruk medan is a management that is carried out to protect the market from waste to make it look clean so that traders and visitors to the traditional market of simpang jeruk medan feel comfortable and protect the community. to avoid various diseases caused by waste, especially in the traditional market of simpang jeruk medan. The type of research used in this study is a type of qualitative research with the type of research used is empirical research. Data collection techniques used by researchers are interviews, observation, and documentation. Data analysis techniques used are data reduction (data reduction), data presentation (data display), and conclusion (verification). Data validity using triangulation is source triangulation, time triangulation, and technical triangulation. The contribution of this paper is for the market community to maintain cleanliness by socializing the impact and legal aspects.